L’artefice delle forme. Un percorso morfologico fra Bonaventura, Alberti e Leonardo da Vinci - Salvestrini, Amalia (Aesthetica Preprint, 2021)
In order to explore forms of Aesthetics in periods before its history, one intends to investigate the aesthetic aspects of the forms maker by focusing on the Bonaventure’s Franciscan thought, which represents a decisive turning point in the diachronic sense of poiesis. A thought that perhaps contributes to both the artistic innovations introduced by Giotto and the Renaissance turn in the concept of the maker observed here in authors such as Leon Battista Alberti and Leonardo da Vinci.